IMPLEMENTATION OF HALAL TOURISM IN AN EFFORT TO IMPROVE THE COMMUNITYS ECONOMY - Ardiyansyah, Amzar; Hanifah, Ida; Nadirah, Ida (Proceeding International Seminar of Islamic Studies, 2023)
The implementation of halal tourism has developed in Indonesia and even other countries have also organized halal tourism. Indonesia is the majority of Muslims, of course, it has great potential for the development of halal tourism, in essence the implementation of halal tourism itself does not limit tourists with various regulations. The role of the government is very large in the development and development of halal tourism to realize the improvement of the community's economy. This paper focuses on how the challenges and opportunities of halal tourism improve the community's economy. This writing method uses the normative juridical method by collecting secondary data through primary, secondary and tertiary materials by studying various books, journals, laws and regulations, documents, websites and writings related to the object of writing. The universe created by Allah SWT needs to be maintained, maintained and managed properly, including in tourism management, in the QS Surah Al-Mulk and Al-Baqarah have explained how to take care of yourself when traveling, hence the importance of the concept of halal tourism. In positive law, the provisions of Article 5 of Law Number 10 of 2009 concerning Tourism clearly state that the relationship between religious, customary, and cultural norms in tourism in each region has its own concept. The government has an important role in the development of halal tourism to improve the community's economy, job opportunities, state and regional income. The improvement of the economy is realized by the government bringing in and offering the concept of halal tourism to investors by providing licensing guarantees and legal certainty to investors to develop halal tourism.